PKM MANAJEMEN FISIOTERAPI PREVENTIVE AND PROMOTIVE POLINEUROPATI PADA LANSIA DI PANTI WREDHA RINDANG ASIH II BONGSARI - Didik Purnomo; Kuswardani Kuswardani; Zainal Abidin (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2025)
This PKM is an effort to increase the knowledge and understanding of the elderly at the Rindang Asih II Bongsari Nursing Home about the management of preventive and promotive polyneuropathy physiotherapy, by holding socialization and promotional and preventive training for neuropathy conditions in the elderly due to diabetes. The main target of this PKM is to provide assistance and train the elderly and caregivers of the Rindang Asih II Bongsari Nursing Home. The methods used range from providing counseling, discussion, socialization, and training on preventive and promotive polyneuropathy methods for the elderly and caregivers of the Rindang Asih II Bongsari Nursing Home on how to prevent pain, control glucose levels, and restore function in elderly neuropathy sufferers due to diabetes. The budget and schedule for the implementation of the proposed community service are very relevant or in accordance with the activities that have been carried out. The activity plan for this PKM program is a) Pre-field survey, b) Preparation of training tools and materials, c) Preparation of understanding methods, d) Socialization and training on preventive and promotive polyneuropathy methods, e) Assistance, f) evaluation, g) Making ongoing programs. Based on the results of the socialization and training, it can be concluded that significant results were obtained, namely that the elderly and caregivers of the Rindang Asih II Bongsari Nursing Home from 20 people who did not understand at all now understand how to carry out preventive and promotive polyneuropathy due to diabetes.